The Predictability Limit of Ocean Mesoscale Eddy Tracks in the Kuroshio Extension Region - Meng, Yao; Liu, Hailong; Ding, Ruiqiang; Lin, Pengfei; Ding, Mengrong; Wang, Pengfei (Frontiers in Marine Science, 2021)
In this study, the nonlinear local Lyapunov exponent and nonlinear error growth dynamics are employed to estimate the predictability limit of oceanic mesoscale eddy tracks quantitatively using three datasets. The results show that the mean predictability limit of OME tracks is about 53 days for cyclonic eddy (CE) and 52 days for anticyclonic eddy (AE) in the Kuroshio Extension (KE). The predictability limit varies spatially. The predictability limit of OME tracks is higher for the eastern region (about 62.5 days) than that for the western part (about 46 days). The CEs (AEs) predictability limit is relatively high in the southern (northern) region. Additionally, the lifetime, amplitude, and radius of OME are closely related to the predictability limit. The long-lived, large-amplitude, and -sized OMEs tend to be more predictable. The eastern region often generates long-lived and large-size OMEs, thereby obtaining a higher predictability limit of OME tracks. Furthermore, the relationship between the predictability limit and the smoothness of the OMEs’ track was investigated using a metric to describe the track's complexation. Usually, OMEs with high predictability limit values often show extender and smoother trajectories. The effects of the surface ocean circulations and the surface winds are also investigated. The strong and energetic currents lead to a short limitation in the west region.